Can there be a market for cheap-talk information? An experimental investigation. - Cabrales, Antonio; Feri, Francesco; Gottardi, Piero; Meléndez-Jiménez, Miguel Ángel (Elsevier, 2020)
This paper reports on experiments testing the viability of markets for cheap-talk information. We find that the level of trade in these markets is very small and eventually vanishes. Sellers provide low-quality information even when doing so does not increase their monetary payoff. This contributes to the low demand in the market for information. Moreover, we observe the same very low level of activity in the market for information when sellers face no conflict of interest and the noise in the quality of the transmitted information is much lower. Hence, we argue that the collapse of the market for information is a demand phenomenon, and even small uncertainty over the quality of information seems to have a large impact.
Artículo publicado en Games and Economic Behavior en el volumen de mayo de 2020 (https://doi.org/doi:10.1016/j.geb.2020.03.002). Se adjunta la versión aceptada, que según SHERPA (https://v2.sherpa.ac.uk/id/publication/15564) puede estar disponible en un repositorio institucional tras un embargo de 24 meses.
Keywords: Juegos, Teoría de; Economía de la información; Experiment; Cheap talk; Auction; Information sale; Information acquisition